DEVELOPING STUDENTS’ SPEECH THROUGH VARIOUS GAMES IN THE OPTIONAL HOURS OF THE MOTHER TONGUE CLASS - Ganiyeva Shodiya Azizovna; Mamajonova Mahliyo Botirjon kizi (Zeta Repository, 2023)
The article describes the concept of speech, the methodology of speech development, and its importance. Ways to develop students’ speech are discussed. Recommendations are given to teachers for the formation of speech culture.